Spirituality and social crisis: a social-philosophical aspects of the study - Сідоркіна O. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article discusses the origins and causes of conflict manifestations of interactions in modern society, shows the socio-philosophical approach to the analysis of crisis phenomena in the society and the spiritual realm.